2014
DOI: 10.1148/radiol.14131374
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of the Prostate and Adjacent Anatomic Structures before, during, and after Ejaculation: Qualitative and Quantitative Evaluation

Abstract: Purpose To determine the possibility of obtaining high-quality magnetic resonance (MR) images before, during, and immediately after ejaculation and detecting measurable changes in quantitative MR imaging parameters after ejaculation. Materials and Methods In this prospective, institutional review board–approved, HIPAA-compliant study, eight young healthy volunteers (median age, 22.5 years), after providing informed consent, underwent MR imaging while masturbating to the point of ejaculation. A 1.5-T MR imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
6
19
0
Order By: Relevance
“…It should be noted that although seminal vesicle fluid makes up 40–85% of the ejaculate [ 15 ], there is also a contribution from the prostate gland (15–30%), testis (<5%) and bulbourethral glands (1–5%); thus, ejaculate volume alone may not provide an accurate indication of changes in seminal vesicle volume. Early work using vesiculography [ 16 ] and ultrasound [ 17 , 18 ] and subsequently confirmed by a more recent MRI study [ 9 ] showed 30–40% reductions in seminal vesicle volume immediately post-ejaculation. However, these studies are not representative of an outpatient MR patient population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that although seminal vesicle fluid makes up 40–85% of the ejaculate [ 15 ], there is also a contribution from the prostate gland (15–30%), testis (<5%) and bulbourethral glands (1–5%); thus, ejaculate volume alone may not provide an accurate indication of changes in seminal vesicle volume. Early work using vesiculography [ 16 ] and ultrasound [ 17 , 18 ] and subsequently confirmed by a more recent MRI study [ 9 ] showed 30–40% reductions in seminal vesicle volume immediately post-ejaculation. However, these studies are not representative of an outpatient MR patient population.…”
Section: Discussionmentioning
confidence: 98%
“…Only one prospective MRI study has documented volume change in this context, demonstrating a 41% mean reduction in SV volume immediately post-ejaculation [ 9 ]. Scanning at this time point is not representative of a clinical MRI study and it is in fact possible that seminal vesicle fluid replacement may occur relatively quickly.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study analysing prostate and SV size found that SV volume decreased by approximately 40% immediately after ejaculation. However, this study examined only pre-ejaculation and immediate post-ejaculation SV volume (Medved et al, 2014). In our study, size as a function of abstinence period between ejaculations is examined, which has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of this claim, however, has not been tested. In a pilot study, Medved et al reported decreased signal intensity on T2-weighted imaging and the apparent diffusion coefficient maps in the peripheral zone after ejaculation, possibly reflecting a reduction in the volume of ejaculatory fluid within the gland [163]. The authors did not observe any dramatic differences in image quality or significant changes in prostate volume after ejaculation.…”
Section: Patient Preparationmentioning
confidence: 93%